2000
DOI: 10.1128/aac.44.5.1276-1283.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Ribavirin Analog ICN 17261 Demonstrates Reduced Toxicity and Antiviral Effects with Retention of both Immunomodulatory Activity and Reduction of Hepatitis-Induced Serum Alanine Aminotransferase Levels

Abstract: The demonstrated utility of the nucleoside analog ribavirin in the treatment of certain viral diseases can be ascribed to its multiple distinct properties. These properties may vary in relative importance in differing viral disease conditions and include the direct inhibition of viral replication, the promotion of T-cell-mediated immune responses via an enhanced type 1 cytokine response, and a reduction of circulating alanine aminotransferase (ALT) levels associated with hepatic injury. Ribavirin also has cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Ribavirin has been shown to diminish viral protein translation and RNA replication via three activities: as a mutagen by incorporation into nascent viral RNA molecules (8)(9)(10)12), by the inhibition of IMP dehydrogenase (IMPDH), which results in a decrease in intracellular GTP levels (25)(26)(27), and by immunomodulatory effects, including a switch in the T-helper cell phenotype from type 2 to type 1 (28)(29)(30)(31)(32). It has been suggested that during virus replication in newly synthesized genomes, a decrease in cellular GTP levels may increase the frequency of ribavirin incorporation in newly synthesized genomes during virus replication through competitive inhibition (9, 10, 12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…Ribavirin has been shown to diminish viral protein translation and RNA replication via three activities: as a mutagen by incorporation into nascent viral RNA molecules (8)(9)(10)12), by the inhibition of IMP dehydrogenase (IMPDH), which results in a decrease in intracellular GTP levels (25)(26)(27), and by immunomodulatory effects, including a switch in the T-helper cell phenotype from type 2 to type 1 (28)(29)(30)(31)(32). It has been suggested that during virus replication in newly synthesized genomes, a decrease in cellular GTP levels may increase the frequency of ribavirin incorporation in newly synthesized genomes during virus replication through competitive inhibition (9, 10, 12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…A minimal direct antiviral activity of ribavirin against HCV and HBV in vitro (Clarysse et al, 1997;Tam et al, 2000) and minimal effect on HCV or HBV virus titres during ribavirin monotherapy (Reichard et al, 1993;Fried et al, 1994;Bodenheimer et al, 1997) suggests that ribavirin has other mechanisms of action. In contrast, the role of immunomodulation by ribavirin in chronic HCV infection may be significant.…”
Section: Compromised or Inappropriate Adaptive Immune Responses In Chmentioning
confidence: 99%
“…Ribavirin may elicit indirect antiviral effects by (1) promoting T-cell mediated immunity against viral infection via the induction of antiviral type 1 cytokines such as IFN-γ, tumour necrosis factor-α (TNF-α) and interleukin-2 (IL-2), and the suppression of proviral type 2 cytokines such as IL-4 and IL-10 ( Tam et al, 1999aTam et al, ,b, 2000 or (2) by affecting the intracellular GTP concentration via inhibition of host inosine monophosphate dehydrogenase (IMPDH) (Streeter et al, 1973;Smith 1980), an effect which presumably inhibits viral RNA synthesis or DNA synthesis in proliferating lymphocytes (Peavy et al, 1980(Peavy et al, , 1981Marquardt et al, 1987). The immunodulatory effects of ribavirin on type 1 cytokines or IMPDH could have a beneficial impact on the immune responses against viral infection.…”
mentioning
confidence: 99%
“…80 Unfortunately, in a recent Canadian randomized controlled multicenter study, high-dose intravenous HCIG, first administered in the anhepatic phase and continued for 48 weeks, had no effect on clinical or virological recurrence in 20 patients who underwent transplantation for HCV cirrhosis. 81 [82][83][84] Viramidine is a livertargeting ribavirin prodrug that is converted to active drug in the liver, thereby reducing RBC accumulation. Hopefully, one of these ribavirin analogues will improve the tolerability of combination therapy in liver transplant recipients.…”
Section: Posttransplantation Prophylaxismentioning
confidence: 99%